"When the earl of Vila Franca does not live in it": the governors of the island of São Miguel (Azores) in the 17th and 18th centuries (Ágora Journal, 2021)
Despite their size, or precisely because of this and due to the fact that islands are spatially well circumscribed territories, and taking into account the political and imperial dynamics of the 16th-18th centuries, on the one hand, and the role of the “economia da graça” in the definition of the relations between the monarchy and the vassals, on the other hand, we believe that insular spaces serve as a good case study either for the analysis of the sociological composition of local elites and the functioning of family networks and inter-personal relationships, or for the analysis of the relationships between the political center (the crown) and local powers (seigniorial or municipal). Thus, taking the insular universe of the Azores as a scale of observation, and in the continuity of previous investigations and ongoing projects, within the framework of a political and social model of the Ancien Regime, we intend to present here a lesser known case, but no less interesting, that of the governors of the island of São Miguel, whose appointment was a privilege of the captains and lords of São Miguel island in the 17th and 18th centuries. Based on an analysis that articulates prosopographic methodology and life histories, this case study reveals the place that this position occupied within a cursus honorum which, in the case of the military, would lead them to positions of greater importance and projection in the context of the Portuguese empire.